The analysis of water management in Bukhara Oasis of Uzbekistan: historical and territorial trends - Abdullaev, Iskandar (2004)
The limited water resources of arid zones are a main constraint on economical development. This is especially true for the Aral Sea disaster zone. Some 1.2 million people are living in the Bukhara oasis, the oldest irrigated zone of Uzbekistan. Irrigation practice in the more than 230,000 ha of land consumes more than 5 km3 of Amu Darya river water. The future development of irrigated agriculture and the environmental situation in the Aral Sea Basin requires analysis of current water management in the irrigated areas of Uzbekistan. Until the 1960s, Bukhara Oasis received water for irrigation from the Zarafshan River, which originates in Tajikistan, flows through Tajikistan, three provinces of Uzbekistan. The Zarafshan River supplied water around 1.2 to 1.5 million hectares of irrigated areas of upper located three provinces of Uzbekistan and for industrial and communal needs of second biggest city of Uzbekistan-Samarqand. Increasing irrigated areas in upper and middle reach of Zarafshan River has impacted the water supply to Bukhara oasis. In the beginning of 1960s, water shortage in the irrigated agriculture of Bukhara Oasis reached its apogee, composing 50 to 55 percent from annual water requirement. As a solution to the water shortage problem of Bukhara oasis, a canal was built from Amu Darya - the largest water body of Central Asia. In the beginning of the 1970s, canal Amu-Bukhara was finished and Bukhara Oasis began to receive water from more reliable source. Further development of the irrigated agriculture in Bukhara Oasis from 1970s fully depended on water supply from Amu-Bukhara canal. The irrigated agriculture of the oasis began to receive more water supply per unit of land, and some new areas have been developed. In the end of the 1980s, Bukhara Oasis faced serious water-environmental problems such as land salinity and water-logging. The land and water productivity declined as an affect of above-mentioned negative impacts of irrigated agriculture. The solutions to the water-environmental problems of the Bukhara Oasis can be only developed through detailed analysis of the past of irrigated agriculture and water management system.This research paper describes stages of development of irrigated agriculture and water management system of Bukhara oasis, tries to analyze general trends, water use, and management changes in the different stages.